A case of arteriovenous hemangioma of the undescended testis - Maeda, Toshihiro (Hinyokika kiyo. Acta urologica Japonica, 2002)
An 8-month-old boy was admitted to our hospital with the complaint of left inguinal pain during his follow-up of left cryptorchism. Computed tomography showed a solid mass with a low density area in the left inguinal region. Tumor markers, including alpha-fetoprotein and human gonadotropin-beta, were normal. Exploration of the left testis by an inguinal approach revealed a reddish mass occupying more than half of the testicular parenchyma and we performed left orchiectomy. The tumor was histopathologically diagnosed as arteriovenous hemangioma